(3bQI Yjhf Phi GdCagGe HTQM ebOeI TjN GdESdGes - (3CHhHcQ Hf ESeGYjd GdTfhGfis; (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdTGaYj , CHh jMji,J (B926 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGd MeO jdjb HLdGdg hHYO ajbhd GdeaJbQ Edi ehdGg hGdZfi Hg s
(3BNQgG (B:s
(3hHYVge ChLH GdhLg GdChd hGddg JYGdi GYde bGd Pdc hcJHg GdabjQ CHhHcQ GdTfhGfi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG hba ddTjN Ydi GdbgGhis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs